THE LOVE SCAMS FRAUD CYBERCRIME IN MALAYSIA: CIVIL LAW AND SYARIAH PERSPECTIVES (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
An increasingly common type of online fraud is "love scams," in which con artists create false online personas with victims to take advantage of them emotionally and financially. These frauds frequently prey on people who use the internet to look for love and companionship. They play on their emotions to win over their trust and then take their money. Love scams are not new, in fact, they are an increasingly common issue with devastating consequences by which in 2018 to June 2023, there were over 7,548 documented cases of love scams, with losses totaling more than RM382 million. This study aims to investigate the factors that lead to love scams, modus operandi used by those who commit them and its relation to the Malaysian civil law as well as the solutions to the fallout from love scams from Syariah perspectives. This research uses a multi-method approach to give light on this complicated issue and to create useful solutions that individuals or victims of love scams can use to lessen its negative effects. A review of various literatures was conducted. Articles and legal documents were also examined to identify relevant provisions of Malaysian civil law and Islamic law that relevant to the issue. This paper concludes with the complex realm of love scams, use a multi-method approach to illuminate the techniques used by the perpetrators, the weaknesses they take advantage of, and the applicable civil and Syariah legal frameworks. By examining the relationship between these legal frameworks and the realities of online fraud, this study aims to empower people who are looking for love online and provide potential victims with self-defense resources.